The last week : the day-by-day account of Jesus's final week in Jerusalem - Borg, Marcus J. (HarperSanFrancisco, 2006)
As scholars Borg and Crossan reacted to questions about the blockbuster film The Passion of the Christ, they discovered that many Christians are unclear on the details of events leading up to the Crucifixion. Here they present a day-by-day account of Jesus's final week of life. They begin their story on Palm Sunday with two triumphal entries into Jerusalem. The first, that of Roman governor Pontius Pilate leading Roman soldiers into the city, symbolized military strength. The second heralded a new kind of moral hero who was praised by the people as he rode in on a humble donkey. The Jesus introduced by Borg and Crossan is this new moral hero, a more dangerous Jesus than the one enshrined in the church's traditional teachings, giving up his life to protest power without justice and to condemn the rich who lack concern for the poor.--From publisher description.